Sulfate reducing bacteria as secondary and necessary pathogens in black band disease of corals - Brownell, Abigael C. (2014)
Black band disease (BBD) is a complex, polymicrobial disease that consists of cyanobacteria, sulfide-oxidizing and sulfate-reducing bacteria (SRB), and heterotrophic bacteria. The cyanobacterium Roseofilum reptotaenium has been implicated as the primary pathogen of BBD, but other consortium members may be secondary pathogens that are necessary to the development of the disease. It is known that populations of the sulfate-reducing bacterium Desulfovibrio are present in BBD and that these populations generate sulfide within the band as a byproduct of dissimilatory sulfate reduction. It is also known that exposure of healthy corals to sulfide leads to cell lysis and coral tissue death. Previous work showed that when freshly collected BBD, which easily infects healthy corals, is exposed to sodium molybdate, a specific inhibitor of sulfate reduction, infection does not occur. In this study we examined the effect of sodium molybdate on infection of corals by a unialgal culture of R. reptotaenium. Coral fragments of Montastraea cavernosa and Siderastrea siderea were transferred into two experimental aquaria, one a control with only artificial seawater (ASW) and the second containing ASW and 2mM sodium molybdate. Small mats of cultured R. reptotaenium were inoculated onto the surface of experimental coral fragments. Both M. cavernosa (n = 6) and S. siderea (n=4) became infected and developed BBD-like infections in the control tank, while there were temporary attachments to, but no successful infection of M. cavernosa (n=3) or S. siderea (n=2) in the experimental tank containing sodium molybdate. The results of this study reveal that a secondary pathogen is essential to the infection process and development of BBD in scleractinian corals. Specifically, SRB such as Desulfovibrio are required for the development of BBD on the coral host. This is the first step in understanding the roles of secondary pathogens in a complex, polymicrobial coral disease. Rev. Biol. Trop. 62 (Suppl. 3): 1-9. Epub 2014 September 01.